Active compliance control of the hydraulic actuated leg prototype. Issue 3 (7th August 2017) - Zhang, Guoteng; Jiang, Zhenyu; Li, Yueyang; Chai, Hui; Chen, Teng; Li, Yibin
Abstract : Purpose: Legged robots are inevitably to interact with the environment while they are moving. This paper aims to properly handle these interactions. It works to actively control the joint torques of a hydraulic-actuated leg prototype and achieve compliant motion of the leg. Design/methodology/approach: This work focuses on the modelling and controlling of a hydraulic-actuated robot leg prototype. First, the design and kinematics of the leg prototype is introduced. Then the linearlized model for the hydraulic actuator is built, and a model-based leg joint torque controller is presented. Furthermore, the virtual model controller is implemented on the prototype leg to achieve active compliance of the leg. Effectiveness of the controllers are validated through the experiments on the physical platform as well as the results from simulations. Findings: The hydraulic joint torque controller presented in this paper shows good torque tracking performance. And the actively compliant leg successfully emulates the performance of virtual passive components under dynamic situations. Originality/value: The main contribution of this paper is that it proposed a model-based active compliance controller for the hydraulic-actuated robot leg. It will be helpful for those robots that aim to achieve versatile and safe motions.